The effectiveness of bay leaf extract (Syzygium polyanthum (Wight) Walp.) as a local food-based nutritional therapy to reduce hypertension in pregnant women - Minarti Minarti; Wa Ode Nesya Jeni Samrida; Sitti Aisyah Ansi (AcTion: Aceh Nutrition Journal, 2026)
Hypertension during pregnancy requires timely management because it can compromise maternal and fetal health. Local food-based plant preparations are often used as complementary approaches, but evidence of their measurable effects on blood pressure in pregnant women remains limited. This study examined changes in systolic and diastolic blood pressure before and after seven days of treatment with Syzygium polyanthum (Wight) Walp. decoction in pregnant women with hypertension. Methods: A quasi-experimental one-group pretest-posttest study was conducted from June to July 2025 in the working area of the Sulaa Primary Health Center, Baubau City, Indonesia. Twenty pregnant women with hypertension, defined as blood pressure ≥140/90 mmHg, were selected using purposive sampling method. The participants received S. polyanthum decoction for seven days. Systolic and diastolic blood pressures were measured before and after the intervention. Data were analyzed using paired sample t-tests. The mean systolic blood pressure decreased from 143.50 ± 2.33 mmHg to 133.95 ± 2.11 mmHg, with a mean reduction of 9.55 mmHg (p < 0.001). The mean diastolic blood pressure decreased from 94.45 ± 1.50 mmHg to 88.60 ± 2.72 mmHg, with a mean reduction of 5.85 mmHg (p < 0.001). In conclusion, a seven-day administration of S. polyanthum decoction was followed by lower systolic and diastolic blood pressure in this one-group study. The decoction may be considered a complementary local food-based approach to support blood pressure management in pregnant women with hypertension; however, randomized controlled studies are needed to confirm its effectiveness and safety.